DEBT RATIO, RETURN ON ASSET, FIRM SIZE AND EARNINGS MANAGEMENT: AGE MODERATION - Soesetio, Yuli; Subagyo, Subagyo; Istanti, Lulu Nurul; Zen, Fadia (Universitas Brawijaya, Indonesia, 2023)
Earnings management still become a phenomenon both in Indonesia and abroad. Many cases of earnings management practices have occurred and the company's amount of leverage is one of the drivers of earnings management practices. This research aims to examine and describe the relationship between various debt policy, profitability, and company size on earning management moderated by firm age. The selected samples were 102 companies listed on the Indonesia Stock Exchange (IDX) in 2010-2018. The independent variables in this study include DER, bank debt, short-term debt and long-term debt, age, and company size. Earnings management as the dependent variable in this study uses the Modified Jones Model. The results of the regression equation analysis show that all debt policy proxies consistently have a negative and significant effect on earnings management. Furthermore, the company's experience as a proxy for firm age strengthens the relationship between debt policy and earnings management practices. More interestingly, specifically among the three debt policies, bank debt is the policy that is most able to represent the influence on earnings management practices. This indicates that the most effective monitoring of earnings management practices comes from banking institutions. Overall, the profit information shown in financial statements is the product of earnings management, so the level of quality of financial reports is deserving of close inspection and prudence when making decisions based simply on profit information.